Supervolcano : eruption - Turtledove, Harry (Roc, 2012)
A supervolcanic eruption in Yellowstone Park destroys crops and livestock, clogs machinery, and makes cities uninhabitable. Those who survive find themselves caught in an apocalyptic catastrophe in which humanity has no choice but to rise from the ashes and recreate the world.